Hubungan Konsumsi Ekstrak Daun Kentang Manis Dengan Produksi ASI Di Laktasi Ibu Di Kabupaten Klaten - Endang Suwanti; Kuswati Kuswati (Poltekkes Kemenkes Surakarta, 2016)
Absctract : Sweet Potatoes Leaf - Breast Milk Production. Breast Milk is a good nutrition for baby. Breast milk important for growing babies. To increase breast milk it is important for mother to consume food like: Katu leaf (sauropus androgynus), sweet potatoes leaf (Ipomoe batatas), Kelor Leaf ( moringa oleifera), fread corn etc. The composition of sweet potatoes leaf is low fat and cholesterol. This leaf is source of proteins, calcium, niacin and iron. Sweet potatoe leaf also contain high fibre, pro vitamins A, vitamin C, riboflamin, vitamin B6, folat, magnecium fosfor, potassium and mangan. It increases breast milk because this leaf contains lagtagagum. The goal of this research is to know the relationship between the consumption sweet potatoes leaf wit breast milk production on lactation mother at Independent Midwife Practice Indarwati, Mranggen and Siti Sujalmi, Socokangsi, Jatinom, Klaten. Methods : Pre=Post test with Control Group. Design : this research measure the influence between experiment and control group during September 2014 until February 2015. Population in this research is all breastfeeding mothers. Sample was taken wih quota sampling wit 15 mothers for intervention group and 15 mothers for control group with inclusive criterion is mothers with normal delivery and healthy newborn babies. Univariat analysis performed to describe the variable with the result is 73.3 % intervention group more produced breast milk compared to control group 13.3%. Bivariat analize to know the relationship between independent and dependent variable by using Pearson Correlation with the statistic result p value= 0.000. Conclusion, There was significant relationship between the consumption sweet potatoes leaf for increasing breast milk production